Radical resection of a giant rib osteosarcoma with complex chest wall reconstruction. (2019) - Ahmad, Sarwat B.; Hoellwarth, Jason; Christie, Neil; Mcgough, Richard
Highlights: A 61-year-old male with a 20 cm primary osteosarcoma of the rib underwent a radical en bloc chest wall resection. Chest wall reconstruction was performed using a poly methyl methacrylate ("bone cement") and polypropylene mesh "sandwich". Functional, cosmetic, and oncologic outcomes at 6 months are excellent. Polypropylene mesh and "bone cement" represent a safe, easy, and affordable approach to reconstructing the rib cage even in cases of large defects. Abstract: Introduction: Primary rib osteosarcoma is a rare chest wall tumor with variable presentation. Large tumors greater than 10 cm are even rarer and present a challenge for surgical management. Presentation of case: A 61-year-old male with a giant osteosarcoma of the left 2 nd rib underwent multidisciplinary management including induction therapy with doxorubicin and cisplatin, followed by en bloc resection with left ribs 1–5, spinous processes of ribs 2–5, small volume lung resection, and chest wall reconstruction with polypropylene mesh and poly methyl methacrylate (PMMA or bone cement). There were no perioperative complications. At 6 months follow-up, the patient remains disease-free. Functional and cosmetic outcome are excellent. Discussion: This 20 cm mass and resection of ribs 1–5 with resulting 25 cm chest wall defect is the largest primary rib osteosarcoma reported in literature. An R0 resection and chest wall reconstruction using polypropylene mesh and bone cement was feasible and safe. Conclusion: Giant chest wall defects involving multi-rib resection can be effectively reconstructed with commonly available and inexpensive polypropylene mesh and PMMA to achieve good cosmetic and functional outcomes.